Upaya Meningkatkan Pemahaman Pendidikan Agama Islam Peserta Didik Kelas Atas SD Negeri 1 Widoro Yang Mengalami Disleksia Menggunakan Media Flashcard - Siti Zubaidah; Siti Fatimah; Atim Rinawati (IAINU Kebumen, 2023)
The purpose of this study was to determine the effectiveness of instructional media using flashcards on the beginning reading ability of students who experience dyslexia to increase their understanding of PAI in SD Negeri 1 Widoro Kec. Karangconnected District. Kebumen. Class action research consists of 2 cycles, there are 2 learning meetings. As for the implementation of classroom action research, it consists of 4 stages, namely the first is the planning stage which includes activities to develop an action plan, which contains an explanation of what (who) and why (why). When (when), where (where), who (by whom), and how (how) to conduct classroom action research. This observation was carried out four times face to face with two cycles. Based on the results of observations of researchers using observation sheets, tests, and interviews. The results of the study showed that through flashcard media it was proven to be able to increase the understanding of PAI in dyslexic elementary school students.